Analisis Analisis Spasial Pengaruh Indikator Ekonomi terhadap Perilaku Tidak Merokok di Jawa Tengah Tahun 2019 - Afrizal Rizqi, Ulul Azmi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Anyone can smoke, both adults and children. Government through several regulations trying to reduce percentage of smoker, including in Central Java Province. Smoking behavior is influenced by several socio-economic factors such as poverty, unemployment and education. This study tries to analyze the effect of socio-economic indicators on smoking behavior in Central Java using spatial analysis. The modeling results show that the Spatial Autoregressive Model is appropriate to describe relationship between dependent and independent variable. The model estimation show the influence of socio-economic indicators toward percentage people who do not smoke. The poverty rate has negative relationship with percentage population who do not smoke. While the unemployment rate and mean years of schooling have a positive relationship with percentage population who do not smoke. The results provide an illustration for government to increase the percentage population who do not smoke through several programs in the socio-economic sector.